2021
DOI: 10.3389/fonc.2021.780906
|View full text |Cite
|
Sign up to set email alerts
|

Potential Clinical Value of Pretreatment De Ritis Ratio as a Prognostic Biomarker for Renal Cell Carcinoma

Abstract: BackgroundWe performed this study to explore the prognostic value of the pretreatment aspartate transaminase to alanine transaminase (De Ritis) ratio in patients with renal cell carcinoma (RCC).MethodsPubMed, EMBASE, Web of Science, and Cochrane Library were searched to identify all studies. The hazard ratio (HR) with a 95% confidence interval (CI) for overall survival (OS) and cancer-specific survival (CSS) were extracted to evaluate their correlation.ResultsA total of 6,528 patients from 11 studies were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
0
6
0
3
Order By: Relevance
“…The current literature investigating the prognostic utility of De Ritis ratio for RCC has produced conflicting findings (7,27), and in our study utilizing a threshold of 2.72, we found De Ritis ratio was significantly associated with all studied outcomes. A meta-analysis by Li et al of 6,528 patients from 11 studies reported a significant association of high pretreatment De Ritis ratio with worse OS (HR 1.41, p<0.001) and CSS (HR 1.59, p<0.001) in patients with renal cell carcinoma (28). The metaanalysis, however, included three studies of patient cohorts treated non-surgically with tyrosine kinase inhibitors or targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current literature investigating the prognostic utility of De Ritis ratio for RCC has produced conflicting findings (7,27), and in our study utilizing a threshold of 2.72, we found De Ritis ratio was significantly associated with all studied outcomes. A meta-analysis by Li et al of 6,528 patients from 11 studies reported a significant association of high pretreatment De Ritis ratio with worse OS (HR 1.41, p<0.001) and CSS (HR 1.59, p<0.001) in patients with renal cell carcinoma (28). The metaanalysis, however, included three studies of patient cohorts treated non-surgically with tyrosine kinase inhibitors or targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Li et al. of 6,528 patients from 11 studies reported a significant association of high pretreatment De Ritis ratio with worse OS (HR 1.41, p<0.001) and CSS (HR 1.59, p<0.001) in patients with renal cell carcinoma ( 28 ). The meta-analysis, however, included three studies of patient cohorts treated non-surgically with tyrosine kinase inhibitors or targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Because the AST level is associated with other organs affected systemically and ALT level specifically indicates parenchymal liver disease, changes in these two enzymes may be useful for the diagnosis or risk stratification of various illnesses [ 9 ]. Serum ratio of AST/ALT, the so-called “De Ritis ratio (DRR)”, has been reported to be a valuable marker in differentiating varying causes of liver disease [ 9 , 13 , 14 ], surrogating different kinds of malignancies [ 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], and provides valuable information on the risk assessment of patients with heart diseases [ 22 , 23 , 24 ], acute kidney injury [ 25 , 26 , 27 ], sepsis [ 28 ], and even patients with COVID-19 [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ischemia-reperfusion injury, oxidative stress, and metabolic disorders can increase serum levels of AST [ 4 , 5 , 6 ]. Therefore, DRR has also been proposed to be valuable in the diagnosis and risk stratification of many illnesses other than liver diseases, including cancers other than hepatoma [ 1 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ], acute kidney injury [ 14 , 15 , 16 ], heart diseases [ 17 , 18 , 19 ], sepsis [ 20 ], and coronavirus disease 2019 (COVID-19) [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%